Customization and acceptability of the WHO labor care guide to improve labor monitoring among health workers in Uganda. An iterative development, mixed method study - Mugyenyi, Godfrey R.; Byamugisha, Josaphat K.; Tumuhimbise, Wilson; Atukunda, Esther C.; Fajardo, Yarine T. (PLOS Global Public Health, 2024)
Cognisant of persistently high maternal and perinatal mortality rates, WHO called for adoption and evaluation of new adaptable and context-specific solutions to improve labor monitoring and health outcomes. We aimed at customizing/refining the new WHO labour care guide (LCG) to suite health care provider needs (HCP) in monitoring labour in Uganda. We used mixed methods to customize/refine and pilot test the new WHO LCG using stakeholder perspectives. Between 1st July 2023 and 30th December 2023, we conducted; 1)30 stakeholder interviews to identify user needs/challenges that informed initial modifications of the WHO LCG; 2)15 HCP in-depth interviews to identify any further needs to modify the LCG; 3) Two focus group discussions and 4) Two exit expert panels to identify any further user needs to further refine proposed modifications into the final prototype. Questionnaires were administered to assess acceptability. We interviewed 125 stakeholders with median age of 36 years (IQR;26–48) exposed to the LCG for at least 12 months with 11.8(SD = 4.6) years of clinical practice. Simple useful modifications/customizations based on format, HCP’s perceived function and role in improving decision making during monitoring labour included; 1) Customizing LCG by adding key socio-demographic data; 2) Adjusting observation ordering; 3) Modification of medication dosages and 4) Provision for recording key clinical notes/ labour outcome data on reverse side of the same A4 paper. All HCPs found the modified WHO LCG useful, easy to use, appropriate, comprehensive, appealing and would recommend it to others for labour monitoring. It was implementable and majority took less than 2 minutes to completely record/fill observations on the LCG after each labour assessment. Active involvement of end-users improved inclusiveness, ownership, acceptability and uptake. The modified LCG prototype was found to be simple, appropriate and easy-to-use. Further research to evaluate large-scale use, feasibility and effectiveness is warranted.
Keywords: WHO; Labor care guide; Labor monitoring; Health workers; Uganda